CRAN-10. PEDIATRIC CRANIOPHARYNGIOMA IN ASSOCIATION WITH FAMILIAL ADENOMATOUS POLYPOSIS. Issue 2 (22nd June 2018) - Dahl, Nathan A; Pratt, Drew; Kumar, Chandan; Camelo-Piragua, Sandra; Mody, Rajen J; Septer, Seth; Hankinson, Todd; Koschmann, Carl; Hoffman, Lindsey
Abstract: Familial adenomatous polyposis (FAP) is a cancer predisposition syndrome that is driven by germline loss-of-function of the APC gene and phenotypically characterized by intestinal polyposis and a variety of extra-intestinal bone and soft tissue tumors. Though craniopharyngioma is not classically associated with FAP, six cases have been reported in adults, all demonstrating ectopic location and adamantinomatous histology. We report the first case of craniopharyngioma associated with FAP in a pediatric patient. A seven-year-old girl with known FAP presented with headache and vomiting and was found on head CT to have partially calcified, cystic mass involving the posterior fossa. MRI delineated a primary suprasellar mass with cystic extension to the pre-pontine space. The cyst was surgically decompressed, and pathology demonstrated an adamantinomatous craniopharyngioma with nuclear β-catenin expression. We performed whole exome sequencing of paired germline and tumor DNA, confirming a CTNNB1 activating point mutation and recapitulation of her germline APC frameshift variant. Whole transcriptome analysis of tumor RNA revealed overexpression of multiple Wnt/β-catenin and SHH pathway genes. This case represents the first FAP-associated craniopharyngioma in childhood and the first characterized with somatic and germline exome sequencing, expanding our understanding of the molecular underpinnings driving tumorigenesis in this unique patient.